Laissez-faire leadership: a comprehensive systematic review for effective education practices - Kamal, Faisal; Ridwan, Ridwan; Ali Rachman Puja Kesuma, Tubagus (Journal of Education and Learning (EduLearn), 2024)
This analysis addresses the knowledge gap on laissez-faire leadership in organizations. After reviewing 64 articles through the systematic literature review, the study finds that laissez-faire leadership, marked by minimal decision-making involvement, is generally associated with negative outcomes like reduced employee satisfaction and productivity. However, its impact can vary based on context, potentially fostering creativity in highly skilled and motivated teams. The study emphasizes the need for judicious application of this leadership style and suggests that school managers should discern when to use it, considering its suitability for different types of educators. Overall, the research contributes valuable insights for leaders aiming to optimize leadership strategies in diverse contexts.